2016
DOI: 10.4314/ejhs.v26i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Safety and analgesic properties of ethanolic extracts of <i>Toddalia asiatica</i> (L) Lam. (<i>rutaceae</i>) used for central and peripheral pain management among the east african ethnic communities

Abstract: BackgroundAlthough herbs are often perceived as “natural” and therefore safe, many different side effects have been reported. Additionally, there is limited scientific evidence to establish the safety and efficacy of most herbal products. The aim of this study was to evaluate the biochemical and haematological effects of Toddaliaasiatica (L) Lam. (Rutaceae) (T. asiatica (L.) in albino Wistar rats.Materials and methodsThe phytochemicals present in the plant were determined. The analgesic activity was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…(Rutaceae) (TA) has been widely used as traditional Chinese medicine for the treatment of various diseases in China ( Yang et al, 2013 ; Tong et al, 2014 ). Modern pharmacologic researches have confirmed that TA extracts have multiple biological activities, including anti-arthritis ( Yang et al, 2013 ), anti-inflammatory ( Hao et al, 2004 ; Balasubramaniam et al, 2011 ; Kariuki et al, 2013 ; Tong et al, 2014 ), anti-microbial ( Narod et al, 2004 ; Duraipandiyan and Ignacimuthu, 2009 ; Karunai Raj et al, 2012 ), anti-parasitic ( Shan et al, 2014 ), anti-oxidant ( Balasubramaniam et al, 2011 ; Irudayaraj et al, 2012 ; Stephen Irudayaraj et al, 2012 ; Ceballos et al, 2013 ), anti-platelet ( Tsai et al, 1998 ), anti-malarial ( Gakunju et al, 1995 ; Oketch-Rabah et al, 2000 ), anti-diabetic ( Irudayaraj et al, 2012 ), anti-tumor ( Iwasaki et al, 2006 ), and analgesic ( Hao et al, 2004 ; Kimang’a et al, 2016 ). TA extracts are mainly composed of coumarins, alkaloids, benzenoids, and their derivatives ( Hu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Rutaceae) (TA) has been widely used as traditional Chinese medicine for the treatment of various diseases in China ( Yang et al, 2013 ; Tong et al, 2014 ). Modern pharmacologic researches have confirmed that TA extracts have multiple biological activities, including anti-arthritis ( Yang et al, 2013 ), anti-inflammatory ( Hao et al, 2004 ; Balasubramaniam et al, 2011 ; Kariuki et al, 2013 ; Tong et al, 2014 ), anti-microbial ( Narod et al, 2004 ; Duraipandiyan and Ignacimuthu, 2009 ; Karunai Raj et al, 2012 ), anti-parasitic ( Shan et al, 2014 ), anti-oxidant ( Balasubramaniam et al, 2011 ; Irudayaraj et al, 2012 ; Stephen Irudayaraj et al, 2012 ; Ceballos et al, 2013 ), anti-platelet ( Tsai et al, 1998 ), anti-malarial ( Gakunju et al, 1995 ; Oketch-Rabah et al, 2000 ), anti-diabetic ( Irudayaraj et al, 2012 ), anti-tumor ( Iwasaki et al, 2006 ), and analgesic ( Hao et al, 2004 ; Kimang’a et al, 2016 ). TA extracts are mainly composed of coumarins, alkaloids, benzenoids, and their derivatives ( Hu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…High doses of plant extracts can be metabolized into toxic end products, which may affect gastric function and reduce food conversion efficiency. 43,44 In the 14 day repeated oral dose toxicity study, Synacinn™ did not affect the intake of food and water, even at the highest dose (2000 mg kg À1 ), particularly during the administration period. Food and water were suitably accepted by the rats treated at all doses of Synacinn™, suggesting that this polyherbal formulation may not cause any alterations to protein, carbohydrate, and fat metabolisms.…”
Section: Discussionmentioning
confidence: 90%
“…The plant roots contain coumarins that have antiplasmodial activity. Toddalia aculeata is used as a pain killer [5]. Till the date several bio-chemicals have been isolated from roots, stems, leaves, flowers, fruits and seeds of this plant and its associating species (Table 1).…”
Section: Medicinal Usesmentioning
confidence: 99%